Age and sex differences in physical activity of portuguese adults and older adults - Bento, Teresa (2023)
This study aims to explore data on objectively measured physical activity from a sample of adults and older adults and to investigate the achievement of the minimum physical activity required for health benefits. Participants, 257 women (age 58.99 ± 18.93 years, BMI 26.75 ± 4.57 kg·m−2 ) and 178 men (age 49.22 ± 20.39 years, BMI 26.81 ± 3.51 kg·m−2 ), wore an accelerometer for 4 to 7 days. Approximately 40% of the time was spent daily in sedentary behaviors during waking hours. Our results do not sustain the suggestion that adult men are more physically active than women. The results indicated a decrease in intensity of physical activity with age, in men and women, but not in successive age groups. Around 75% of adults and 30% of older adults accumulated the minimum daily physical activity for health benefits, in periods shorter than 10 min, above moderate intensity. The number of steps taken per day revealed that most men and women (except the oldest) attained or exceeded the lower threshold for deriving health benefits. To obtain relevant health benefits, future physical activity interventions should aim at reversing the amount of sedentary behaviors, emphasizing increments in, at least, the lower levels of PA, and maintaining walking habits.